UTILIZING JIGSAW METHOD TO IMPROVE LEARNING ACTIVITIES AND STUDENTS’ HISTORY LEARNING OUTCOME AT CLASS XII IPS (SOCIAL SCIENCE) OF SMA NEGERI 10 PEKANBARU - Julita Marta; Raja Usman (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this study was to improve students’ learning activities and learning outcomes through two cycles of action. An initial test was conducted before the implementation of the learning process. The total score in the pre-cycle was 2390, increased to 2885 in cycle I, and further increased to 3070 in cycle II. Meanwhile, the average score in the pre-cycle was 68.29, which increased to 78.92 in cycle I and to 87.71 in cycle II. These scores were measured based on the minimum learning mastery criterion (KKM) of 80. In the pre-cycle, only 8 students (22.86%) achieved the KKM, while 27 students (77.14%) did not. In cycle I, 24 students (68.57%) reached the KKM, and 11 students (31.43%) had not yet achieved mastery. Furthermore, in cycle II, 34 students (97.14%) reached the KKM, and only 2.86% of students did not. The highest score in the pre-cycle was 85 and the lowest was 45, while in cycle I the highest score increased to 95 and the lowest score to 75. Based on the range and criteria of scores, the percentage in the pre-cycle was 31.43% (enough), increased to 37.14% (very high) in cycle I, and further increased to 51.43% (very high) in cycle II. In addition, students’ learning activities also increased in each cycle, reaching 71.43% in cycle I and 85.71% in cycle II. It can be concluded that the jigsaw method was effective in improving learning activities and students’ learning outcomes in class XII IPS of SMA Negeri 10 Pekanbaru.